Clinical manifestations of the female athlete triad among some Iranian athlete - Movaseghi, S.; Dadgostar, H.; Dahaghin, S.; Chimeh, N.; Alenabi, T.; Dadgostar, E.; Davatchi, F. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The study`s purpose was to evaluate clinical manifestations of the female athlete triad among some elite Iranian athletes.